Chemically integrated hierarchical hybrid zinc cobaltate/reduced graphene oxide microspheres as an enhanced lithium-ion battery anode. Issue 6 (11th January 2016) - Chen, Chang; Liu, Borui; Ru, Qiang; Ma, Shaomeng; Hu, Shejun; Hou, Xianhua
Abstract : ZnCo2 O4 /rGO hybrid composites synthesized by an alcoholization process, together with hierarchical microsphere zinc cobalt oxides (ZCO) embedded in the graphene sheets, can display superior rate capability and enhanced cyclic stability during cycling. Abstract : Chemically integrated hierarchical microsphere ZnCo2 O4 /reduced graphene oxide hybrid composites are synthesized via a polyol process. Microsphere ZnCo2 O4 particles embedded in graphene homogeneously with sizes in the region of 320–512 nm, graphene sheets grew and interwove inversely in the inside of the microsphere ZnCo2 O4 particles, so that the structure possesses a unique microsphere–sheet hybrid structure. The interconnected graphene conductive network basic skeleton is beneficial to the transportation of Li + and electrons. Compared with the conventional way metal oxides and graphene combine, hierarchical microsphere ZnCo2 O4 /reduced graphene oxide hybrid composites exhibit enhanced rate capability (469.7 mA h g −1 at 4000 mA g −1 ) and long term cycling ability with high capability (904.2 mA h g −1 at 1000 mA g −1 over 500 charge/discharge cycles), owing to the special characteristic of a three-dimensional structure. Most importantly, with the successful synthesis of the hierarchical microsphere ZnCo2 O4 /reduced graphene oxide hybrid composites, this facile strategy can extend to the synthesis of the ternary transition metal oxides/reduced graphene oxide with hierarchical microsphere structure and make it possible to explore a more promising storage application.